Prevalence of Anemia and Its Associated Risk Factors Among 6-Months-Old Infants in Beijing - Li, Qinrui; Liang, Furong; Liang, Weilan; Shi, Wanjun; Han, Ying (Frontiers in Pediatrics, 2019)
Objective The worldwide prevalence of anemia is approximately 24.8%. Iron-deficiency anemia is common in children and women and is associated with sensory, motor, cognitive, language and social-emotional deficits. Therefore, detection and early intervention strategies for anemia in infants are urgently needed. To prevent the occurrence of iron deficiency anemia, we aimed to identify risk factors associated with anemia in infants. Methods This investigation was a cross-sectional study of 6-month-old infants discharged between April 2014 and September 2017 from Peking University First Hospital. We assessed birth information, maternal age, and maternal educational level as well as data on feeding style, complementary foods and primary caregivers. The infants were assessed with the Denver Developmental Screening Test (DDST). Results A total of 1127 6-month-old infants were enrolled at the hospital. We found that the prevalence of anemia among infants in Beijing was approximately 11.8%. Premature infants had a higher rate of anemia than full-term infants (χ2=40.103, P<0.001). Infants born in autumn or winter were at an elevated risk of developing anemia (χ2=22.949, P <0.001). Birth weight had no effect on the rate of anemia in infants (χ2=0.023, P=0.568). Infants who were exclusively breastfeeding had higher anemia rates than infants who were fed formula (χ2=38.466, P<0.001). Infants whose caregivers added no complementary foods had higher anemia rates (24.7%) than those whose caregivers added more than two kinds of complementary food (8.2%). The type of caregiver had no effect on the anemia rate in infants (χ2=0.031, P=1.000). Conclusions The following factors resulted in a higher prevalence of anemia in our study: a gestational age at birth of less than 37 weeks, exclusive breastfeeding, a lack of supplementation with complementary foods and a spring birth date. No significant differences in DDST pass rates were evident between infants with and without anemia.